Boosted Lithium-Ion Transport Kinetics in n-Type Siloxene Anodes Enabled by Selective Nucleophilic Substitution of Phosphorus - Kim, Se In; Kim, Woong‑Ju; Kang, Jin Gu; Kim, Dong‑Wan (Nano-Micro Letters, 2024)
Doped two-dimensional (2D) materials hold significant promise for advancing many technologies, such as microelectronics, optoelectronics, and energy storage. Herein, n-type 2D oxidized Si nanosheets, namely n-type siloxene (n-SX), are employed as Li-ion battery anodes. Via thermal evaporation of sodium hypophosphite at 275 °C, P atoms are effectively incorporated into siloxene (SX) without compromising its 2D layered morphology and unique Kautsky-type crystal structure. Further, selective nucleophilic substitution occurs, with only Si atoms being replaced by P atoms in the O3≡Si–H tetrahedra. The resulting n-SX possesses two delocalized electrons arising from the presence of two electron donor types: (i) P atoms residing in Si sites and (ii) H vacancies. The doping concentrations are varied by controlling the amount of precursors or their mean free paths. Even at 2000 mA g−1, the n-SX electrode with the optimized doping concentration (6.7 × 1019 atoms cm−3) delivers a capacity of 594 mAh g−1 with a 73% capacity retention after 500 cycles. These improvements originate from the enhanced kinetics of charge transport processes, including electronic conduction, charge transfer, and solid-state diffusion. The approach proposed herein offers an unprecedented route for engineering SX anodes to boost Li-ion storage. Highlights: 1 Extrinsic doping is proposed as a novel route to enhance the intrinsic properties of the two-dimensional oxidized Si nanosheet (namely, siloxene) anode for Li-ion batteries. 2 Fabrication of P-doped n-type siloxene is revealed to be possible through selective nucleophilic substitution of Si atoms in siloxene with P atoms. 3 Due to boosted charge transport kinetics, n-type siloxene (6.7 × 1019 P atoms cm-3) exhibits the excellent storage performance (594 mAh g-1 after 500 cycles) even at 2000 mA g-1.